DESAIN SARANA BUDIDAYA LALAT BLACK SOLDIER FLY (BSF) - Yoga Bayu Pangestu; Moch. Junaidi Hidayat (Universitas Mercu Buana, 2022)
Black Soldier Fly larvae has a voracious appetite and processes from maggot Black Soldier Fly can be used to make compost from household waste and agricultural waste. The purpose of this research is to produce a product for the cultivation of Black Soldier Fly that can help reduce the amount of household wet waste and make it easier for cultivators to cultivate Black Soldier Fly flies.This research uses qualitative and quantitative research methods. In the qualitative method, the researcher conducted interviews with BSF , namely Sudi BSF and Omah Maggot Surabaya, then the results of the survey, observation and documentation from the two case study sites were used as reference data in this study. Qualitative data obtained from questionnaires, journals, books and online media are used as a reference in making products. The result of this research is the design of a Black Soldier Fly fly cultivation process Black Soldier Fly starting from the egg laying process to the harvest process.